Author's correction: LST8 regulates cell growth via target-of-rapamycin complex 2 (TORC2) - Wang, Tao; Edgar, Bruce (Molecular and cellular biology, 2012)
Volume 32, no. 12, p. [2203-2213][1], 2012. Page 2209, [Fig. 5C][2]: This panel was inadvertently a duplicate of panel B. The correct data are shown below. This change does not affect any of the results or conclusions of our study. We apologize for any confusion this error might have caused. - - ![
Published online July 18, 2012
Gesehen am 23.11.2020